TERMS OF ENSURING QUALITY OF THE RAILWAY WHEELS BUILT UP BY WELDING - Haivoronskyi, O. A. (Science and Transport Progress, 2016)
Purpose. The paper assumes to set the basic laws in determining the structure and physical-mechanical properties of wheel steels during arc welding technology and to develop the recommendations for reconstruction of railway wheel wear surfaces that will improve the reliability and safety of traffic in terms of increasing operating loads. Methodology. To achieve this purpose the paper studied 1) the influence of operating loads on structural changes and properties of metal wheels; 2) the impact of arc welding on structural and phase composition and properties of the metal heat-affected zone, its resistance to brittle and slow fracture; 3) the impact of welded metal on the formation of the stress state of the welds and their resistance to formation cracks; 4) wear resistance of built up metal during friction-slip of the «wheel-rail» pair. Findings. The most intense zone of the rolling profile of freight railway wheels during operation is a place of transition from rolling surface to the ridge. Therefore, the wheel building up by welding requires first of all the increased resistance to brittle fracture of metal in this area. It is established that welding in the metal of the wheel heat-affected zone cause formation of the hardened bainite-martensite structures. The minimum metal cooling rate, at which the martensite start forming is 8°C / s (in the range of 600…500°C) when the content of carbon in steel is 0.58% and 2°C/s at 0.65% of carbon. It is shown that to increase resistance to cracking it is necessary to limit the cooling rate to 16.0°C/s when the carbon content is C < 0.60% and to 8.0°C / s when C = 0.60…0.65%. Under these conditions, the metal has rather high ability to mikroplastic deformation without cracking. It was founded that to improve the critical stress intensity factor К1С at brittle fracture it is necessary to provide conditions when welding would result in the built up structure that does not contain upper bainite and the martensite share does not exceed the number of lower bainite (ratio of M/Bn < 1). It is proved that exposure of wheels within 3.5-4.5 hours at 100°C after welding, during their slow cooling improves resistance to brittle fracture of metal heat-affected zone by 1.8-2.3 times. This is due to the removal of diffusion hydrogen from the metal and reduction of the ІІ type stress in the lath volume of bainite and martensite by 1.5. Originality. The author has developed the idea of the structural-phase changes that occur in the metal of railway wheels during arc welding. The relation between the carbon content in steel, cooling rate during welding and resistance to cracking and brittle fracture was found. The authors determined the influence of after-welding wheel cooling conditions on the metal properties. Practical value. Technological recommendations for railway freight wheel building up by welding were developed. Their application will improve quality of the railway wheels built up by welding, reliability and safety of traffic in conditions of growing operating loads.